Cerebrovascular co-pathology and cholinergic white matter pathways along the Lewy body continuum - Jerele, Cene; Tzortzakakis, Antonios; Nemy, Milan; Rennie, Anna; Arranz, Javier; Montal, Victor; Bejanin, Alexandre; Aarsland, Dag; Westman, Eric; Fortea, Juan; Lleó, Alberto; Alcolea, Daniel; et al. (Brain communications, 2025)
Dementia with Lewy bodies often presents with cholinergic degeneration and varying degrees of cerebrovascular disease. There is a lack of radiological methods for evaluating cholinergic degeneration in dementia with Lewy bodies. We investigated the potential of the Cholinergic Pathway Hyperintensities Scale (CHIPS) in identifying cerebrovascular disease-related disruptions in cholinergic white matter pathways, offering a practical and accessible method for assessing cholinergic integrity in neurodegenerative diseases. We assessed the associations of CHIPS with regional brain atrophy, Alzheimer's disease co-pathology and clinical phenotype. Additionally, we compared its diagnostic performance to that of other manual and automated evaluation methods. We included 82 individuals (41 patients in the Lewy body continuum with either probable dementia with Lewy bodies or mild cognitive impairment with Lewy bodies, and 41 healthy controls) from the Sant Pau Initiative on Neurodegeneration cohort. We used CHIPS to assess cholinergic white matter signal abnormalities (WMSA) on MRI, while tractography mean diffusivity provided a complementary measure of cholinergic WMSA. For global WMSA evaluation, we used the Fazekas scale and FreeSurfer. CHIPS successfully identified cerebrovascular disease-related disruptions in cholinergic white matter pathways, as evidenced by its association with tractography and global WMSA markers (P < 0.005 for all associations). Lewy body patients showed a significantly higher degree of WMSA in the external capsule cholinergic pathway despite no significant differences in global WMSA compared to controls. CHIPS score in the posterior external capsule and the mean diffusivity in the external capsule and cingulum exceeded the threshold for an optimal biomarker (sensitivity and specificity values above 80%) in discriminating Lewy body patients from controls. Furthermore, higher CHIPS scores, Fazekas scale and tractography mean diffusivity were associated with more pronounced frontal atrophy in Lewy body patients but not in controls. No associations were found for the four WMSA and integrity methods with the core clinical features, clinical or cognitive measures, or CSF biomarkers. In conclusion, cholinergic WMSA were more pronounced in Lewy body patients compared to healthy controls, independently of global WMSA. Our findings indicate that cerebrovascular disease-related disruptions in cholinergic white matter may be linked to frontal atrophy in Lewy body patients. Clinically, we demonstrate the potential of CHIPS to assess cholinergic WMSA using widely available MRI sequences. Our data suggest cerebrovascular disease co-pathology could drive the cholinergic degeneration in Lewy body patients, opening opportunities for therapeutic interventions targeting vascular health from mild cognitive impairment with Lewy bodies through manifest dementia with Lewy bodies.
Keywords: cholinergic white matter pathways; CHIPS; white matter signal abnormalities; dementia with Lewy bodies